Hitting the thesis wall: demotivation hindering graduate students’ research completion - Catama, Bryan Vinoya; Tejada, Nelwyn Lalicon (Journal of Education and Learning (EduLearn), 2025)
Research conducted by graduate students is crucial for the development of lifelong learning skills and future professional success. However, many students encounter obstacles that hinder the timely completion of their research projects and theses. The factors that impede the completion of research papers within designated timeframes have not been thoroughly investigated, resulting in a lack of understanding of certain barriers. This qualitative phenomenological study aimed to identify the demotivating factors that hinder graduate researchers from completing their research papers on time. Through thematic analysis of qualitative data from 10 purposively selected graduate students experiencing demotivation, the findings provide a comprehensive understanding of the personal, psychological, institutional, and resource-related factors that demotivate graduate researchers. Key issues include self-determination challenges, conflicting responsibilities, rigid policies, and inadequate support. These insights can guide interventions to enhance graduate student achievement, well-being, and research productivity. By addressing the diverse barriers identified, academic institutions can create a more supportive environment for graduate researchers to excel.